2008
DOI: 10.1111/j.1399-5448.2008.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment satisfaction but no difference in metabolic control when using continuous subcutaneous insulin infusion vs. multiple daily injections in children at onset of type 1 diabetes mellitus

Abstract: Objective:  The aim of this study was to compare safety, metabolic control, and treatment satisfaction in children/adolescents at onset of type 1 diabetes mellitus who were treated with either continuous subcutaneous insulin infusion (CSII) or multiple daily injections (MDI). Research design and methods:  Seventy‐two children/adolescents (7–17 yr of age) were enrolled in this open, randomized, parallel, multicenter study. Approximately half of the patients were treated with MDI (natural protamine hagedorn [NPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 33 publications
5
96
1
1
Order By: Relevance
“…Our data confirm that CSII improved the lipid profile, but we also demonstrated that CSII is much better than MDI in improving lipid parameters. on the other side, our data are in contrast with what recently reported by skogsberg et al [30]: they admitted that CSII improves treatment satisfaction in patients, but they say that there is no difference in metabolic control when using Csii compared to mDi. probably, the reason of this difference is due to the fact that they used a more aggressive MDI, administering five shots each day and using lispro and NPH insulin, while we administered four shots each days with mDi using lispro and glargine insulin.…”
Section: Lipid Profilecontrasting
confidence: 56%
“…Our data confirm that CSII improved the lipid profile, but we also demonstrated that CSII is much better than MDI in improving lipid parameters. on the other side, our data are in contrast with what recently reported by skogsberg et al [30]: they admitted that CSII improves treatment satisfaction in patients, but they say that there is no difference in metabolic control when using Csii compared to mDi. probably, the reason of this difference is due to the fact that they used a more aggressive MDI, administering five shots each day and using lispro and NPH insulin, while we administered four shots each days with mDi using lispro and glargine insulin.…”
Section: Lipid Profilecontrasting
confidence: 56%
“…Similar results were seen in A1c among adolescents over 12 years of age, while less difference was seen among children 12 years of age and younger ( Figure 1). Also, no significant difference was observed between CSII and MDI in measures for daytime 29,31,36 and nocturnal hypoglycemia 35,36 (low strength of evidence), severe hypoglycemia 29 (low strength of evidence), frequency of hyperglycemia 37 (insufficient strength of evidence), and ratio of basal to bolus The mean between-group difference in fasting glucose over 6 months was -12.3 mg/dL (95% CI, -32.9 to 8.2; P = NS) favoring CSII in 1 study, 38 while 2 other studies reported no difference in fasting glucose between the intervention groups (low strength of evidence). 43,44 Additionally, the mean betweengroup difference in pre-prandial glucose over 6 months was -17.1 mg/dL (95% CI, -42.1 to 8.0; P = NS) favoring CSII in 1 study, 38 and in another study, pre-dinner glucose was lower with CSII (128 mg/dL) compared with MDI (148 mg/dL) at the end of 5 weeks (P = NS).…”
Section: Children and Adolescents With T1dmmentioning
confidence: 96%
“…35 When examining diabetes treatment-related quality of life, as assessed by Diabetes Treatment Satisfaction Questionnaire (DTSQ), a meta-analysis of 2 studies favored CSII over MDI (mean between-group difference, 5.7; 95% CI, 5.0-6.4; P < 0.001), although the variation in the effect due to heterogeneity was significant (low strength of evidence). 29,37 The investigators of the review did not find any studies addressing certain process measures (frequency of adjusting…”
Section: Assessments Of Study Quality and Strength Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Many more blood glucose testing strips should be supplied to enable HBGM at least three times a day. Insulin pump therapy may make management more convenient and avoid the many needle pricks, but according to Skogsberg et al, [8] while there is improved patient satisfaction there is no difference in metabolic control with pump therapy v. multiple daily injections. Several metaanalyses show a statistical difference in favour of pump therapy, but only amounting to a minimal improvement of 0.2 -0.3% in HbA1c values.…”
Section: Discussionmentioning
confidence: 99%